2015
DOI: 10.4172/2161-0495.1000265
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins, Ochratoxins, Trichotecenes, Patulin, Fumonisins and Beauvericin in Finished Products for Human Consumption

Abstract: Mycotoxins are considered a serious threat for mankind health due to their ability to form toxic secondary metabolites. For this reason, many efforts are actually in progress to reduce their impact on food, feed and food chain by-products. In particular, a large part of the scientific investigation is focused on reducing the on field contamination using an in situ agronomic approach or specific biological tools. In this paper, the reduction of Aflatoxins (AFs), Ochratoxins (OTAs), Trichothecenes (TC), Patulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…They present diverse chemical structures, having different biological effects on animals and humans, such as teratogenicity, carcinogenicity, mutagenicity, immunotoxicity or neurotoxicity [1,2]. These toxic compounds are often naturally occurring in the food chain and, therefore, result in human exposure either by direct consumption of contaminated Studies show that mycotoxins are ubiquitous contaminants [28,29]. It is estimated that they are present in approximately 25% of cereals consumed worldwide and a recent study suggests that this percentage could be even higher [30].…”
Section: Introductionmentioning
confidence: 99%
“…They present diverse chemical structures, having different biological effects on animals and humans, such as teratogenicity, carcinogenicity, mutagenicity, immunotoxicity or neurotoxicity [1,2]. These toxic compounds are often naturally occurring in the food chain and, therefore, result in human exposure either by direct consumption of contaminated Studies show that mycotoxins are ubiquitous contaminants [28,29]. It is estimated that they are present in approximately 25% of cereals consumed worldwide and a recent study suggests that this percentage could be even higher [30].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely documented that although many mycotoxins are thermally stable compounds, some food processing, such as applying temperatures above 100 C, can reduce their amount (Raiola & Ritieni, 2014;Raiola, Tenore, Manyes, Meca, & Ritieni, 2015;Santini, Raiola, Meca, & Ritieni, 2015;Shanakhat et al, 2018;Vidal, Sanchis, Ramos, & Marín, 2015). Among the known thermal processing techniques, variations on fluidized bed drying are extensively applied for particulate drying at industrial scales in both traditional and innovative processed products, since it is a cost-effective technique providing a high thermal efficiency (Jangam, 2011).…”
mentioning
confidence: 99%
“…Research done by Pietri, et al [11] showed that fumonisin concentrations were lower in the cleaned maize than the unprocessed kernels. Santini, et al [16] also noted that cleaning, if done effectively, reduces fumonisins concentrations from the pericarp as well as from the damaged and broken grains by 50 %. Matumba, et al [17] and Kimanya, et al [18] also allude to the fact that sorting of maize prior to milling reduces contamination of maize by fumonisins since defective kernels are discarded.…”
Section: Survey Resultsmentioning
confidence: 99%